STUMP DIAMETER CHARACTERISTICS AND VOLUME PREDICTION FOR Acacia mangium IN BA VI, VIETNAM - Manh Hung, Bui; Thi Bich Phuong, Nguyen; Sy Doanh, Le; The Hai, Phung (Journal of Forestry Science and Technology, 2021)
Tree stump diameter plays a big role in forest resource management. The study used data from 23 plots. The results showed that the acacia community was classified into 2 clusters. The stump diameter mean of cluster 1 is larger than cluster 2. The stump diameter frequency distribution of cluster 1 was more right-skewed. The research tested five theoretical distributions including: Normal, Lognormal, Weibull, SHASH, Johnson. Analyzed results indicated that the Weibull distribution was the best for modeling the stump diameter frequency distribution. The correlation between the base diameter and the diameter at breast height, total height, and tree volume was best described by the Power function. Between the stump diameter and the diameter at breast height, the parameters of the Power equation for cluster 1 were 0.669 and 1.056. Meanwhile, these parameters of cluster 2 were 0.708 and 1.041. However, the Cubic equation was the best for describing the regression between the base diameter and the total height of cluster 2. The Power function has also been used to build 2 volume prediction tables for 2 clusters. These tables will help forest rangers in Ba Vi and other areas with similar conditions to tracing the volume of lost trees, contributing to sustainable and effective forest management.